Decision Making in the Perspective of Sundanese Culture and Its Implications in Guidance and Counseling - Fatimah, Siti; Suminar, Riani (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
This study aims to analyze career decision-making skills from a Sundanese cultural perspective which is characteristic of Sundanese culture, Sundanese people's interests are synonymous with less challenging career choices and the difficulty of making career decisions because they adhere to the life principle "Kudu ngukur ka julur" (must adjust to one's own abilities) and “Tong sok getas harupateun” (don't take steps rashly). This is contrary to one of the Sundanese cultural values, namely the singer which means being a proactive person with a high work ethic, and is skilled. The conclusion of this study is that career decision making will have an impact on overall and sustainable career satisfaction, regardless of cultural background which includes gender and ethnicity. In making career decisions, each individual thinks about his career and how his thought processes will affect his career, especially those related to interests, abilities, values, job preferences, and the world of work. For this reason, career counseling guidance is here to help each individual make career-related decisions and effectively manage a career during their lifetime, including developing emotional resilience to overcome challenges that arise as their work life progresses